A comparative study of genotyping and antimicrobial resistance between carbapenem-resistant Klebsiella pneumoniae and Acinetobacter baumannii isolates at a tertiary pediatric hospital in China - Xiaoli Jian; Yunyun Li; Haiping Wang; Cuilian Li; Feng Li; Jue Li; Jing Dong; Tingyi Du; Li Jiang (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundCarbapenem-resistant Klebsiella pneumoniae (CRKP) clinical isolations have rapidly increased in pediatric patients. To investigate a possible health care-associated infections of CRKP in a tertiary pediatric hospital, the circulating clones and carbapenem-resistant pattern between CRKP and carbapenem-resistant Acinetobacter baumannii (CRAB) isolates were compared to classify their epidemiological characteristics. The results will help to identify the epidemic pattern of the CRKP transmission in the hospital.MethodsNinety-six CRKP and forty-eight CRAB isolates were collected in Kunming Children’s Hospital from 2019 through 2022. These isolates were genotyped using repetitive extragenic palindromic-PCR (REP-PCR). Carbapenemase phenotypic and genetic characterization were investigated using a disk diffusion test and singleplex PCR, respectively. In addition, these characteristics of the two pathogens were compared.ResultsThe rates of CRKP and CRAB ranged from 15.8% to 37.0% at the hospital. Forty-nine and sixteen REP genotypes were identified among the 96 and 48 CRKP and CRAB isolates tested, respectively. The CRKP isolates showed more genetic diversity than the CRAB isolates. Of the 96 CRKP isolates, 69 (72%) produced Class B carbapenemases. However, all 48 CRAB isolates produced Class D carbapenemase or extended-spectrum β-lactamases (ESBL) combined with the downregulation of membrane pore proteins. Furthermore, the carbapenemase genes blaKPC, blaIMP, and blaNDM were detected in CRKP isolates. However, CRAB isolates were all positive for the blaVIM, blaOXA-23, and blaOXA-51 genes.ConclusionsThese CRKP isolates exhibited different biological and genetic characteristics with dynamic changes, suggesting widespread communities. Continuous epidemiological surveillance and multicenter research should be carried out to strengthen the prevention and control of infections.